Graphene Quantum Sheet Catalyzed Silicon Photocathode for Selective CO2 Conversion to CO. (2nd December 2015) - Yang, Ki Dong; Ha, Yoonhoo; Sim, Uk; An, Junghyun; Lee, Chan Woo; Jin, Kyoungsuk; Kim, Younghye; Park, Jimin; Hong, Jung Sug; Lee, Jun Ho; Lee, Hye‐Eun; Jeong, Hui‐Yun; et al.
Abstract : The reduction of carbon dioxide (CO2 ) into chemical feedstock is drawing increasing attention as a prominent method of recycling atmospheric CO2 . Although many studies have been devoted in designing an efficient catalyst for CO2 conversion with noble metals, low selectivity and high energy input still remain major hurdles. One possible solution is to use the combination of an earth‐abundant electrocatalyst with a photoelectrode powered by solar energy. Herein, for the first time, a p‐type silicon nanowire with nitrogen‐doped graphene quantum sheets (N‐GQSs) as heterogeneous electrocatalyst for selective CO production is demonstrated. The photoreduction of CO2 into CO is achieved at a potential of −1.53 V versus Ag/Ag +, providing 0.15 mA cm −2 of current density, which is 130 mV higher than that of a p‐type Si nanowire decorated with well‐known Cu catalyst. The faradaic efficiency for CO is 95%, demonstrating significantly improved selectivity compared with that of bare planar Si. The density functional theory (DFT) calculations are performed, which suggest that pyridinic N acts as the active site and band alignment can be achieved for N‐GQSs larger than 3 nm. The demonstrated high efficiency of the catalytic system provides new insights for the development of nonprecious, environmentally benign CO2 utilization. Abstract : Highly selective CO2 to CO photoconversion catalyzed by N‐doped graphene quantum sheets (N‐GQSs) on a p‐type Si nanowire is demonstrated. The photocatalytic system produces CO with the chemical selectivity of more than 95%, which is comparable with that of the noble metals such as Au and Re. The developed system provides a new means for utilizing CO2 as a usable chemical feedstock.